A new species of Galerina (Hymenogastraceae, Agaricales) from northeast China - Liu, Xiaoliang; Bau, Tolgor (Phytotaxa, 2021)
Galerina variibasidia, a new species in the Hymenogastraceae, was discovered in Arxan, Inner Mongolia Autonomous Region, China. This species is presented with morphological description, illustrations, and supported by phylogenetic analyses using Maximum Likelihood and Bayesian Inference analyses with the internal transcribed spacer rDNA sequences.